Early to Middle Bronze Age agricultural terraces in north-east England: morphology, dating and cultural implications. (April 2023) - Brown, Antony G.; Fallu, Daniel; Cucchiaro, Sara; Alonso-Eguiluz, Monica; Albert, Rosa Maria; Walsh, Kevin; Pears, Ben R.; Scaife, Rob; Langdon, Catherine; Tarolli, Paolo; Cockroft, David; Snape, Lisa; et al.
Abstract: Abstract : Terracing is found widely in the Mediterranean and in other hilly and mountainous regions of the world. Yet while archaeological attention to these 'mundane' landscape features has grown, they remain understudied, particularly in Northern Europe. Here, the authors present a multidisciplinary study of terraces in the Breamish Valley, Northumberland. The results date their construction to the Early to Middle Bronze Age, when they were built by cutting back the hillside, stone clearance and wall construction. Environmental evidence points to their use for cereal cultivation. The authors suggest that the construction and use of these terraces formed part of an Early to Middle Bronze Age agricultural intensification, which may have been both demographically and culturally driven.